(untitled) (KONFERENSIYA, 2025)
This article deals with one of the urgent problems of modern linguistics. That is related to media-discourse and its types. As we know, the main type of discourse is media-discourse. The article focuses on essential features of media-discourse by pointing out types including press, TV, internet media. Media-discourse has become a global space of conveying messages by distributing information to the public, besides it is the tool to persuade individuals in society by making them grasped to the intended ideology